Human Nature in Self-Identity Construct: A Meta-ethnography Study - Rahma Ayuningtyas Fachrunisa; Bagus Riyono (Buletin Psikologi, 2023)
The development of identity theories in psychology tends to be partial and incoherent, and are followed by various problems. This study uses meta-ethnography to deconstruct theories of self-identity in order to find common threads and relation between theories, including main theories on identity (Erikson’s; Marcia’s), and other related theories (Berzonsky’s, Grotevant’s, Waterman’s, McAdams’s), This study uses Hofstede's (2001) view on identity theories, and formulates a fundamental and comprehensive conceptualization of identity theory. This study formulates a model of the layers of identity which includes the identity of (1) human nature, (2) personal, and (3) social. This study also explains the dynamics of the self as ‘I’ and ‘Me’ in the formation of identity. This study discusses human nature in the discourse of identity and this provides further implications in the field of developmental psychology and educational psychology.